A PET based fluorescent chemosensor with real time application in monitoring formaldehyde emissions from plywood. Issue 24 (31st May 2018) - Gangopadhyay, Ankita; Maiti, Kalipada; Ali, Syed Samim; Pramanik, Ajoy Kumar; Guria, Uday Narayan; Samanta, Sandip Kumar; Sarkar, Ripon; Datta, Pallab; Mahapatra, Ajit Kumar
Abstract : A simple, robust fluorescent chemodosimeter capable of detecting nanomolar levels of formaldehyde with applicability in monitoring formaldehyde emissions from plywood. Abstract : An easily synthesized (7-nitrobenz-2-oxa-1, 3-diazole) NBD piperazine conjugate, NPC, has been successfully employed for the fluorogenic sensing of the hazardous substance, formaldehyde (FA), based on the inhibition of photoinduced electron transfer (PET) as a consequence of formimine creation, which was proven by ESI-MS analysis. The probe has been found to be highly selective with a low response time of 2 min. The robust sensorNPC has been used to demonstrate its practical applicability in detecting vapor phase FA through emissions from plywood samples. The cell permeability has also been exploited to demonstrate the possibility of intracellular FA estimation using this probe.